Potential of Bay Leaf (Syzygium polyanthum) Extract as Bioinsecticide Against Aedes aegypti - Fitria Funny, Vianita; Sulistio, Irwan; Suprijandani, Suprijandani; Marlik, Marlik; Suranta Sinulingga, Teguh (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Pesticides contribute to environmental pollution, health problems, and resistance. Bioinsecticides offer an alternative solution. This study evaluated the potential of bay leaf juice (Syzygium polyanthum) as a bioinsecticide in the 2024 efficacy test against Aedes aegypti mosquitoes. This research is pseudo-experimental, with a post-test only control group design. The object of this study was female Aedes aegypti mosquitoes aged 2–5 days. This study used replication 5 times. The variables of this study were the variation of bay leaf juice 12%, 17%, 22%, 27%, 32%, and the number of deaths of Aedes aegypti mosquitoes after one hour. Data were analysed using One Way Anova. Bay leaf juice has the potential to kill Aedes aegypti mosquitoes. Variations in the concentration of bay leaf juice caused significant differences in the mortality of Aedes aegypti mosquitoes. The concentration of bay leaf juice at 31.136% is LC50, and the concentration of bay leaf juice at 52.803% is LC95. Other researchers can test the active ingredients of bay leaf juice that have the highest effect on killing Aedes aegypti mosquitoes.